Pengaruh Gaya Kepemimpinan Transaksional Dan Penilaian Kinerjaterhadap Produktivitas Kerja (Studi Kasus Pegadaian Syariah Wilayah Yogyakarta) - Dyah Piklanti Diwanti; Putry Diana Diana (AGHNIYA : Jurnal Ekonomi Islam, 2020)
This study aims to analyze the effect of transactional leadership style and performance appraisal on work productivity in PegadaianSyariah of Yogyakarta Region. This research uses a quantitative approach using primary data and secondary data. The analytical tool used is multipe linear regression to test the hypothesis with the help of SPSS application version 22. The population in this study was employees at PegadaianSyariah, and the number of samples used amounts to 40 respondents taken using total/saturated sampling techniques. The results of this study partially indicate that the variables of transactional leadership style and performance appraisal have a positive and significant effect on work productivity variables. Simultaneously the transactional leadership style and performance appraisal have a significant effect on work productivity in PegadaianSyariah of Yogyakarta Region.